THE USE OF INTERACTIVE TECHNOLOGY IN ISLAMIC EDUCATION AT ELEMENTARY SCHOOLS: IMPACT ON STUDENTS' MOTIVATION, PARTICIPATION, AND UNDERSTANDING - Devi Melani (CV. Fahr Publishing, 2023)
This study aims to evaluate the impact of using interactive technology in Islamic Education (PAI) at elementary schools on students' motivation, participation, and understanding. Utilizing a mixed-method research design, data were collected through questionnaires, semi-structured interviews, and classroom observations. The results showed a significant increase in students' learning motivation from 60% to 85%, participation from 55% to 90%, and conceptual understanding from 58% to 87% after implementing interactive technology. Teachers reported that interactive learning media facilitated material delivery and increased student engagement. However, challenges such as inadequate facilities and teachers' technical skills need to be addressed to maximize the benefits of this technology. In conclusion, interactive technology can enhance the quality of PAI learning and shape better student character with proper support from various stakeholders